Historical analysis of the recovery of physical functionality in a coral reef community following the implementation of active restoration practices - Muñoz-Alfaro, Adahara (2026)
Introduction: The Reef Functional Index (RFI) is a tool used to analyze the physical functionality of coral assemblages based on morpho-functional traits that support their geo-ecological roles. This tool has been applied to assess the effects of active restoration on coral reefs under varying levels of stress. However, to date, it has not been used to analyze long-term assisted recovery through restoration activities. Objective: This study evaluated the historical trajectory of physical functionality over the long term (2012–2023) in six coral reef communities within the Islas Marietas National Park (PNIM), considering that active restoration efforts have been in place since 2014, using the RFI as a metric. Methods: The RFI was used as an indicator of physical functionality to assess temporal changes in reef condition throughout the analysis period. The percentage of natural change and change subsidized by restoration was calculated for both RFI and live coral cover (LCC). Results: RFI values revealed that although coral communities in the PNIM had, by 2023, regained LCC levels exceeding those recorded in 1997, physical functionality had not yet been fully restored. Restoration activities have contributed to approaching historical functional values, even under the impact of various natural stressors; however, spatial analysis at the island and site level indicated that recovery has not been uniform. Conclusions: The findings highlight the need to review and adapt restoration strategies, emphasizing greater efforts in sites where coral functionality remains below pre-disturbance levels. Additionally, the results demonstrate that the RFI is a valuable tool for evaluating the long-term success of coral restoration and identifying potential areas of opportunity in degraded reef sites.